Renaissances : the one or the many? - Goody, Jack (Cambridge University Press, 2010)
One of the most distinguished social scientists in the world addresses one of the central historical questions of the past millennium: does the European Renaissance deserve its unique status at the very heart of our notions of modernity? Jack Goody scrutinises the European model in relation to parallel renaissances that have taken place in other cultural areas, primarily Islam and China, and emphasises what Europe owed to non-European influences. Renaissances continues that strand of historical analysis critical of Eurocentrism that Goody has developed in recent works like The East and the West (1996) or The Theft of History (2006). This book is wide-ranging, powerful, deftly argued, and draws upon the author's long experience of working in Africa and elsewhere. Not since Toynbee in The Study of History has anybody attempted quite what Jack Goody is undertaking in Renaissances, and the result is as accessible as it is ambitious -- Présentation de l'éditeur.